AF710B, an M1/sigma‐1 receptor agonist with long‐lasting disease‐modifying properties in a transgenic rat model of Alzheimer's disease. Issue 6 (29th December 2017) - Hall, Hélène; Iulita, Maria Florencia; Gubert, Palma; Flores Aguilar, Lisi; Ducatenzeiler, Adriana; Fisher, Abraham; Cuello, Augusto Claudio
Abstract: Introduction: AF710B (aka ANAVEX 3‐71) is a novel selective allosteric M1 muscarinic and sigma‐1 receptor agonist. In 3×Tg‐AD mice, AF710B attenuates cognitive deficits and decreases Alzheimer‐like hallmarks. We now report on the long‐lasting disease‐modifying properties of AF710B in McGill‐R‐Thy1‐APP transgenic (Tg) rats. Methods: Chronic treatment with AF710B (10 μg/kg) was initiated in postplaque 13‐month‐old Tg rats. Drug or vehicle was administered orally daily for 4.5 months and interrupted 5 weeks before behavioral testing. Results: AF710B long‐term treatment reverted the cognitive deficits associated with advanced Alzheimer‐like amyloid neuropathology in Tg rats. These effects were accompanied by reductions in amyloid pathology and markers of neuroinflammation and increases in amyloid cerebrospinal fluid clearance and levels of a synaptic marker. Importantly, these effects were maintained following a 5‐week interruption of the treatment. Discussion: With M1/sigma‐1 activity and long‐lasting disease‐modifying properties at low dose, AF710B is a promising novel therapeutic agent for treating Alzheimer's disease.